The Evidence-Based Midwife Professionalism - Fitriani Nur Damayanti1 , Absori Absori2 , Kelik Wardiono2 , Sri Rejeki1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Midwife professionalism is the basic social contract between a midwife and society so that professionalism is considered to be very important. There are some cases related to midwife professionalism. Midwife as health practitioner should understand about midwifery practice very well. The midwife should realize that she works based on regulation and law. Material and Method: The study was aimed to find out the professionalism in midwifery practice. Non Doctrinal research was used as the research approach. The sample was taken with non-probability sampling, which is a snowball technique. Findings: 93% of midwifery practices were qualified to administer code of ethics, 86% of midwifery practices were qualified to administer responsibility of midwifery practice, 93% of midwifery practices were qualified to precise collaboration and reference for midwifery practice, all the midwifery practices were qualified to administer continuing education in order to improve midwifery care, 93% of midwifery practices were qualified to competence for midwifery practice, 53% of midwifery practices were qualified to administer advocacy. Conclusion: It can be concluded that the midwifery practice has fulfilled the professionalism indicators such as profession code of ethics, responsibility, precise collaboration and reference, continuing education, and competence. Nevertheless, there were some professionalism indicators which have not been fulfilled. It was giving advocacy. It was due to the lack of knowledge and comprehension about advocacy in midwifery practice.